Anogenital warts and relationship to child sexual abuse: Systematic review and meta‐analysis. Issue 4 (1st June 2021) - Awasthi, Smita; Ornelas, Jennifer; Armstrong, April; Johnson, Jennifer A.; Eisen, Daniel B.
Abstract: Background/Objectives: In children, distinguishing anogenital warts (AGW) acquired innocently from those acquired by child sexual abuse (CSA) is challenging. High‐quality studies examining this relationship are sparse. Here, we sought to evaluate the association between AGW and sexual abuse in children 12 years of age and younger with respect to wart location, age, and gender. Methods: A systematic review of Ovid MEDLINE, Embase, and Web of Science was performed for studies published on or before 2/16/2018. Studies were eligible for inclusion if they contained at least 10 patients 12 years old and younger and reported the number of patients who were sexually abused. The principal summary measures were the odds ratios (OR) of reported CSA with respect to subject age, wart location, and gender. Results: Three hundred twenty‐seven studies were identified through record search. Twenty five were included in a summary synthesis (791 subjects); 10 were included in the final statistical analysis (199 subjects). In our overall review, 102 of 468 (21%) females and 36 of 204 (18%) males with AGW were abused or probably abused. Overlapping HPV types were found in abused and non‐abused subjects. Perianal location and gender were not significant predictors of abuse. Both age and genital wart location (penis, vulva) did significantly predict CSA (α = .05). The odds ratio for sexual abuse of children aged 3‐4 years was 7.45; 6.52 for ages 5‐8 years; and 6.93 for ages 9‐12 years compared to those 0‐2 years of age. Genital location was associated with an OR of CSA of 5.93. Conclusions: Our systematic review supports a significant association between AGW in a child greater than 2 years of age and odds of CSA. Genital wart location significantly predicts CSA as well. HPV typing is not a reliable method to ascertain CSA. Male family members and acquaintances were the most likely perpetrators of abuse.